nynw.net
ǰλãҳ >> Ϊʲôsin2x=2sinxCosx >>

Ϊʲôsin2x=2sinxCosx

ϸдֽ

֤̣ 2sinxcosx =sinxcosx+sinxcosx=sinxcosx +cosxsinx=sin(x+x)=sin2x Ǻʽ֤幫ʽ£ 1sin(A+B)=sinAcosB+cosAsinB 2sin(A-B)=sinAcosB-sinBcosA 3cos(A+B)=cosAcosB-sinAsinB 4cos(A-B...

ij˷ (sin2x)'=(2sinxcosx)'=(2sinx)'cosx+2sinx(cosx)' =2cosxcosx+2sinx(-sinx) =2(cosx^2-sinx^2) =2cos2x Ϻ󵼷 2x=t, (sin2x)'=(sint)'(2x)'=2cost=2cos2x=2(cosx^2-sinx^2)

sin(x+x)=sinxcosx+cosxsinx=2sinxcosx cos(x+x)=cosxcosx-sinxsinx=(cosx)^2-(sinx)^2 ֱӺͼ1=(sinx)^2+(cosx)^2 sin2x=2sinxcossin(a+b)=sinacosb+cosasinbƳ cos2x=1-(2sinx)^2 or (2cosx)^2-1,ͬ cos(a+b)=cosacosb-...

ԴӺͽǹʽôƵ sin2x=sin(x+x) =sinxcosx+cosxsinx =2sinxcosx

lim[(sin2x)/x]=lim[(2sinxcosx)/x]=lim{[(2sinx)/x]•cosx}

Ȼ

Сֵ- 3(3)/2 £ f(x)=sin2x+2sinx f'(x)=2cos2x+2cosx=4(cosx)^2+2cosx-2=2(2cosx-1)(cosx+1) f'(x)=0ʱf(x)ڼֵ ʱ2cosx-1=0 cosx=1/2 sinx= (3)/2 -(3)/2 sin2x=2sinx*cosx=(3)/2...

(2sinxcosx)=(sin2x)'=2cos(2x)=(cosƽx-sinƽx)

ΪcosX- cos3X =cos(2x-x)-cos(2x+x) =cos2xcosx+sin2xsinx -(cos2xcosx-sin2xsinx) =2sin2xsinx

վҳ | վͼ
All rights reserved Powered by www.nynw.net
copyright ©right 2010-2021
磬ַϵͷzhit325@qq.com